Endgame, 1945 : the missing final chapter of World War II - Stafford, David (Back Bay Books, 2007)
A narrative chronicle of the three months following VE Day traces the experiences of nine individuals who witnessed the Allied struggle to bring the war to a close, covering such topics as the deaths of Hitler and Mussolini and the liberation of Dachau.